Complete Denture Prosthodontics Treatment and Problem Solving (Springer International Publishing, 2018)
This excellently illustrated book equips dental students and practitioners with all the information and guidance required in order to ensure successful implementation of complete denture treatment in edentulous patients following appropriate treatment planning. Readers will find detailed guidance on tooth selection and arrangement, the try-in stage, and remounting and occlusal adjustment. Potential short- and long-term postinsertion problems are identified, with clear explanation of how to resolve them. Information is also provided on the use of stress-reducing materials for complete dentures. The final part of the book is devoted to techniques that can be employed in problematic cases. The text is supported by a wealth of high-quality photographs drawn from the authors' own extensive clinical experience. A companion volume covering every aspect of the planning stage is available separately.